2022
DOI: 10.2147/orr.s359844
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma on Type I Collagen Production, VEGF Expression, and Neovascularization after Femoral Bone Implants: A Study on Rat Models

Abstract: Platelet-rich plasma (PRP) contains many growth factors, such as FGF, which induces the production of type I collagen, and VEGF, which induces neovascularization, all of which are important in bone healing. This study aimed to evaluate the effect of PRP administration on type I collagen production, VEGF expression, and neovascularization in rat models following femoral bone implants using K-wire. Methods: An experimental randomized control study was conducted on 24 white male rats (Rattus norvegicus) in the Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is consistent with this case, as our patient reported decreased pain every visit after his injection. Finally, one last mechanism worth mentioning regarding the healing properties of platelet releasate is the stimulation of collagen production from fibroblasts, which can promote the formation of new, stronger tendon tissue [ 11 ]. Platelet releasate contains fibroblast growth factor (FGF), which is responsible for extracellular matrix and collagen synthesis, which is important for the regeneration of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with this case, as our patient reported decreased pain every visit after his injection. Finally, one last mechanism worth mentioning regarding the healing properties of platelet releasate is the stimulation of collagen production from fibroblasts, which can promote the formation of new, stronger tendon tissue [ 11 ]. Platelet releasate contains fibroblast growth factor (FGF), which is responsible for extracellular matrix and collagen synthesis, which is important for the regeneration of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have suggested efficacy of PRP and CBT in the treatment of chondral injuries [2, 8, 11, 14], less evidence is available investigating their effects on the healing of acetabular labral repairs. In theory, the increased neovascularization and collagen production associated with PRP usage could stimulate the healing process after a labral repair [16, 42].…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve patient outcomes, orthobiologics such as hyaluronic acid (HA), platelet‐rich plasma (PRP), and cell‐based therapies (CBT) have been proposed as an adjunct treatment modality for FAIS [24, 48]. While the evidence regarding their mechanism of action continues to evolve, proposed benefits of these various orthobiologics for musculoskeletal disorders include pain relief, inhibition of the intra‐articular inflammatory cascade, and stimulation of soft‐tissue healing [4, 5, 9, 11, 12, 16, 21, 25, 42].…”
Section: Introductionmentioning
confidence: 99%